A cross-sectional study on the perceived barriers to physical exercise among women in Iraqi Kurdistan Region - Sherzad A. Shabu; Mariwan H. Saka; Dara A. Al-Banna; Sahar M. Zaki; Hamdia M. Ahmed; Nazar P. Shabila (BMC, 2023)
Abstract Background Limited research has investigated the barriers to physical exercise among women in Iraqi Kurdistan Region and other similar Muslim and Middle Eastern societies. This study aimed to determine the prevalence of perceived barriers to physical exercise among women and examine the associations of these barriers with the participants' sociodemographic characteristics. Methods A cross-sectional study was carried out in Erbil, Iraqi Kurdistan Region, from December 2022 to January 2023. A self-administered online survey was designed using Google Forms. A convenience sample of 500 women and girls aged 18-65 years was selected for the study. A questionnaire was designed for data collection, including a list of 21 potential barriers to physical exercise developed based on literature review and experts' opinions. The barriers were divided into three categories: interpersonal (8 barriers), social environment (8 barriers), and built environment factors (5 barriers). The participants were asked to indicate for each potential barrier whether it was "not really a barrier, somewhat a barrier, or a very important barrier." The statistical package for social sciences was used to estimate the prevalence of different barriers and assess their association with sociodemographic characteristics using the Chi-square test. Results The prevalence of physical inactivity among the study participants was 68.2%. The most prevalent interpersonal barriers to physical exercise included lack of time (47.4%), followed by fatigue (24%), and cost (22.4%). Regarding social environment factors, work (30.6%), harassment outside (22.2%), not having a friend or family member accompanying (19%), and not being allowed by family (15.4%) were the most prevalent barriers to physical exercise. Lack of footpaths, cycle lanes, or parks (34.4%), limited accessibility of gyms or other exercise facilities (25.8%), and environmental pollution (21%) were the most prevalent built environment factors as barriers to physical exercise. Conclusion Women in Iraqi Kurdistan Region experience many barriers to physical exercise. Women require family and social support and awareness about exercise benefits to overcome interpersonal and social environment barriers to physical exercise. Built environment factors are very important barriers and can be reduced by taking appropriate action and adopting necessary policies to provide the required infrastructure and facilities for physical exercise.